A subset of octopaminergic neurons that promotes feeding initiation in Drosophila melanogaster. - Hyesoo Youn; Colleen Kirkhart; Justine Chia; Kristin Scott (PLoS ONE)
Octopamine regulates feeding behavioral responses in Drosophila melanogaster, however the molecular and circuit mechanisms have not been fully elucidated. Here, we investigated the role of a subset of octopaminergic neurons, the OA-VPM4 cluster, in sucrose acceptance behavior. Thermogenetic activation of Gal4 lines containing OA-VPM4 promoted proboscis extension to sucrose, while optogenetic inactivation reduced extension. Anatomically, the presynaptic terminals of OA-VPM4 are in close proximity to the axons of sugar-responsive gustatory sensory neurons. Moreover, RNAi knockdown of a specific class of octopamine receptor, OAMB, selectively in sugar-sensing gustatory neurons decreased the behavioral response to sucrose. By calcium imaging experiments, we found that application of octopamine potentiates sensory responses to sucrose in satiated flies. Taken together, these findings suggest a model by which OA-VPM4 promotes feeding behavior by modulating the activity of sensory neurons.